Efficiency optimisation in a DC-DC chopper motor drive - Prest, Rory Bruce (Department of Electrical Engineering, 2023)
A complete DC-DC motor drive (battery, chopper, and motor) - is investigated with a view to optimising efficiency. The losses at each stage are analysed in detail and proposals are made to minimise them. The overall system is also modelled for the purpose of computer simulation. The computer model is used to investigate the possible efficiency saving if both field and armature current are controlled. An optimum control system is developed and compared with other control systems.